2007
DOI: 10.1111/j.1526-4610.2007.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Distraction Versus Spatial Discrimination on Laser‐Evoked Potentials in Migraine

Abstract: Migraine patients exhibited reduced inhibition by attentional modulation of pain processing, accompanied by impaired spatial discrimination of painful stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
3
25
1
Order By: Relevance
“…Previous studies, evaluating the distraction from experimental pain induced by the vision of positive, neutral, negative, and pain-related pictures in chronic syndromes, as fibromyalgia, somatoform pain disorder and back pain, found that affective modulation of pain was not specifically altered in these patients (Arnold et al, 2008). A reduced inhibitory effect induced by an alternative cognitive task was observed in migraine, especially in regard to laser evoked responses, with a similar trend for pain rating (de Tommaso et al, 2003(de Tommaso et al, , 2008a. It may be argued that emotional stimuli are able to distract migraine patients from pain, independently from their affective content, and probably due to a cognitive engagement connected with the content of the images, which contrast pain sensation.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Previous studies, evaluating the distraction from experimental pain induced by the vision of positive, neutral, negative, and pain-related pictures in chronic syndromes, as fibromyalgia, somatoform pain disorder and back pain, found that affective modulation of pain was not specifically altered in these patients (Arnold et al, 2008). A reduced inhibitory effect induced by an alternative cognitive task was observed in migraine, especially in regard to laser evoked responses, with a similar trend for pain rating (de Tommaso et al, 2003(de Tommaso et al, , 2008a. It may be argued that emotional stimuli are able to distract migraine patients from pain, independently from their affective content, and probably due to a cognitive engagement connected with the content of the images, which contrast pain sensation.…”
Section: Discussionmentioning
confidence: 66%
“…In our previous studies on healthy volunteers, we have recently observed that images are able to distract from pain, on the basis of their aesthetic content (de Tommaso et al, 2008b). In fact, there is a cognitive-attentiveattraction toward beautiful images, also the geometric ones, demonstrated by the amplitude increase of the cognitive ERP P3 (de Tommaso et al, 2008a). In the case of emotional images, the effect on pain induced by emotive experience may be quite variable across people, depending upon picture content and modality of presentation (Mühlberger et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, LEPs are abnormally modulated by heterotopic conditioning stimuli such as remote capsaicin application [8] and by distraction [9,10].…”
Section: Pain-related Responsesmentioning
confidence: 99%